Follicular Helper T Cells in DiGeorge Syndrome - Klocperk, Adam; Paračková, Zuzana; Bloomfield, Markéta; Rataj, Michal; Pokorný, Jan; Unger, Susanne; Warnatz, Klaus; Šedivá, Anna (Frontiers in Immunology, 2018)
DiGeorge syndrome is an immunodeficiency characterized by thymic dysplasia resulting in T cell lymphopenia. Most patients suffer from increased susceptibility to infections and heightened prevalence of autoimmune disorders, such as autoimmune thrombocytopenia. B cells in diGeorge syndrome show impaired maturation with low switched-memory B cells and a wide spectrum of antibody deficiencies or dysgammaglobulinemia, presumably due to impaired germinal center responses. We set out to evaluate the circulating follicular helper T cells (cTFHs) in diGeorge syndrome, as markers of T-B interaction in the germinal centers in a cohort of 17 patients with partial diGeorge and 21 healthy controls of similar age. cTFHs were characterized as CXCR5+CD45RA- CD4+ T cells using flow cytometry. We verify previous findings that the population of memory CD4+ T cells is relatively increased in diGeorge patients, corresponding to low naïve T cells and impaired T cell production in the thymus. The population of CXCR5+ memory CD4+ T cells (cTFHs) was significantly expanded in patients with diGeorge syndrome, but only healthy controls and not diGeorge syndrome patients showed gradual increase of CXCR5 expression on cTFHs with age. We didn’t observe any correlation between cTFHs and serum IgG levels or the population of switched memory B cells. There was no difference in cTFH numbers between diGeorge patients with/without thrombocytopenia and with/without allergy. Interestingly, we show strong decline of PD1 expression on cTFHs in the first 5 years of life in diGeorge patients and healthy controls, and gradual increase of PD1 and ICOS expression on CD4- T cells in healthy controls later in life. Thus, here we show that patients with diGeorge syndrome have elevated numbers of cTFHs, which however do not correlate with autoimmunity, allergy or production of IgG. This relative expansion of cTFH cells may be a result of impaired T cell development in patients with thymic dysplasia.